A Comparatively Experimental Study on the Performance and Emission Characteristics of a Diesel Engine Fueled with Tung Oil-Based Biodiesel Blends (B10, B20, B50) - Zhiyue Mu; Jianqin Fu; Feng Zhou; Kainan Yuan; Juan Yu; Dan Huang; Zhuangping Cui; Xiongbo Duan; Jingping Liu (Energies, 2023)
In this paper, the performance and emission characteristics of a diesel engine were investigated with varying ratios of tung oil-based biodiesel blends (B10, B20, and B50) and neat diesel under different operating conditions. The experimental results showed that the addition of biodiesel blends had different effects on engine power and torque depending on the blend ratio. B10 displayed a slight increase in power and torque, which increased by 1.9% and 6.6%. At the same time, B20 and B50 showed declines slightly. The fuel consumption rate increased slightly with an increasing percentage of biodiesel added. In general, all the blends exhibited significantly lower emissions of CO, NOX, HC, and smoke compared to neat diesel. B10 displayed the most notable reduction of CO emissions, with a 42.86% decrease at medium to high loads. NOX emissions of tung oil-based biodiesel blends were reduced at all load conditions except for B50. In addition, HC emissions were all reduced, especially for B20, which led to a 27.54% reduction at 50% load. Among all the tested blends, B50 showed the greatest decrease in smoke emissions of 38.05% compared to neat diesel at 2000 rpm. The research concluded that using biodiesel fuels from renewable resources, such as tung oil, presents a promising environmentally friendly alternative fuel option.